Novel diagnostic markers for periprosthetic joint infection: a systematic review - Schindler, Melanie; Walter, Nike; Maderbacher, Guenther; Sigmund, Irene K.; Alt, Volker; Rupp, Markus (Frontiers in Cellular and Infection Microbiology, 2023)
Background Identifying novel biomarkers that are both specific and sensitive to periprosthetic joint infection (PJI) has the potential to improve diagnostic accuracy and ultimately enhance patient outcomes. Therefore, the aim of this systematic review is to identify and evaluate the effectiveness of novel biomarkers for the diagnosis of PJI. Methods We searched the MEDLINE, EMBASE, PubMed, and Cochrane Library databases from January 1, 2018, to September 30, 2022, using the search terms “periprosthetic joint infection,” “prosthetic joint infection,” or “periprosthetic infection” as the diagnosis of interest and the target index, combined with the term “marker.” We excluded articles that mentioned established biomarkers such as CRP, ESR, Interleukin 6, Alpha defensin, PCT (procalcitonin), and LC (leucocyte cell count). We used the MSIS, ICM, or EBJS criteria for PJI as the reference standard during quality assessment. Results We collected 19 studies that analyzed fourteen different novel biomarkers. Proteins were the most commonly analyzed biomarkers (nine studies), followed by molecules (three studies), exosomes (two studies), DNA (two studies), interleukins (one study), and lysosomes (one study). Calprotectin was a frequently analyzed and promising marker. In the scenario where the threshold was set at ≥50-mg/mL, the calprotectin point-of-care (POC) performance showed a high sensitivity of 98.1% and a specificity of 95.7%. Conclusion None of the analyzed biomarkers demonstrated outstanding performance compared to the established parameters used for standardized treatment based on established PJI definitions. Further studies are needed to determine the benefit and usefulness of implementing new biomarkers in diagnostic PJI settings.